1990
DOI: 10.1007/bf02423504
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of cranial vessels excites nociceptive neurones in several thalamic nuclei of the cat

Abstract: Extracellular recordings were made in the thalamus of cats anaesthetized with chloralose and urethane following electrical, mechanical and chemical stimulation of the superior sagittal sinus or middle meningeal artery. Facial receptive fields were looked for using electrical and mechanical stimuli. The locations of fifty-six cells were verified histologically. Twenty six cells were located in the ventroposteromedial nucleus (VPM) and six in its ventral periphery (VPMvp). All units in VPM had facial receptive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 59 publications
3
37
1
Order By: Relevance
“…Using anatomical, physiological, histological and pharmaceutical techniques, such animal studies have demonstrated the presence of dura-sensitive neurons in brain and spinal cord structures, such as the medullary dorsal horn, thalamus, hypothalamus, periaqueductal gray (PAG) 15,17-24. In the medullary dorsal horn25,26 and thalamus27,28 the majority of these trigeminovascular neurons respond to noxious skin stimuli either preferentially (wide-dynamic range neurons) or exclusively (high-threshold neurons). Administration of anti-migraine drugs such as ergotamines, triptans, or CGRP antagonists have been shown to inhibit responses to electrical stimulation of the dura in dura-sensitive neurons in the medullary dorsal horn 19,29-31…”
Section: Experimental Activation Of Trigeminovascular Pathwaysmentioning
confidence: 99%
“…Using anatomical, physiological, histological and pharmaceutical techniques, such animal studies have demonstrated the presence of dura-sensitive neurons in brain and spinal cord structures, such as the medullary dorsal horn, thalamus, hypothalamus, periaqueductal gray (PAG) 15,17-24. In the medullary dorsal horn25,26 and thalamus27,28 the majority of these trigeminovascular neurons respond to noxious skin stimuli either preferentially (wide-dynamic range neurons) or exclusively (high-threshold neurons). Administration of anti-migraine drugs such as ergotamines, triptans, or CGRP antagonists have been shown to inhibit responses to electrical stimulation of the dura in dura-sensitive neurons in the medullary dorsal horn 19,29-31…”
Section: Experimental Activation Of Trigeminovascular Pathwaysmentioning
confidence: 99%
“…Such studies have recorded neuronal responses to dural stimulation in the trigeminal nerve (Bove and Moskowitz, 1997) or ganglion (Dostrovsky, 1991;Strassman et al, 1996), medullary and upper cervical dorsal horn Dostrovsky, 1986, 1988a;Strassman et al, 1986;Lambert et al, 1991;Kaube et al, 1992;Burstein et al, 1998), and the ventrobasal thalamus (Davis and Dostrovsky, 1988b;Zagami and Lambert, 1990). Studies in our laboratory have examined response properties of dural afferent neurons in the trigeminal ganglion that can be activated by electrical stimulation of dural sites over the transverse sinus (Strassman et al, 1996;Strassman and Raymond, 1999;Levy and Strassman, 2002a, b).…”
mentioning
confidence: 95%
“…Wind-up ( fi g. 1 ) very specifi cally refers to an increase in neuronal responses with subsequent stimuli to A ␦ or C fi bre afferents that has a hyperbolic function with a typical plateau after approximately twenty stimuli. Interestingly we have recently been able to record typical wind-up in trigeminal 12 neurons with responses to electrical stimulation of facial receptive fi elds but not in any trigeminal neurons we studied with electrical stimulation to the dura mater, either for A ␦ or C fi bre inputs [35] . One must be cautious in a negative study but it is curious that intracranial nociceptive afferents do not easily exhibit wind-up.…”
Section: Central Sensitisationmentioning
confidence: 99%